The Effect of NPK Doses and Plant Spacing on Lettuce (Lactuca sativa L.) Growth and Production - R. Rahmawati (Agrotech Journal, 2020)
The aim of this study was to determine the impact of NPK doses and proper plant spacing in lettuce growth and production. The experiment was conducted in Wirimpalennae Village, Tempe Subdistrict, Wajo Regency from January to March 2017. The experiment employed randomized block design with 2 factor factorial namely NPK doses (300 kg/ha, 350 kg/ha, 400 kg/ha and plant spacing (20 x 25 cm, 25 x 25 cm, 25 x 40 cm). The result showed that the interaction between NPK doses and plant spacing were significantly influenced the fresh weight of lettuce. The highest yield of lettuce was 2,16 kg/Ha (12 t/Ha) produced by the combination of NPK dose (350 kg/ha) and plant spacing (25 x 25). The interaction of NPK dose and plant spacing treatments were not significantly influenced others parameters